A Literature Review of Qualitiy of Work Life - Handayani, Meliana (Health Notions, 2018)
The purpose of the present study is to explore the consequences of quality of work life. It systematically searched and collected studies related to quality of work life and it consequences. QWL is useful for improving and reducing job stress, employers can also make more effective efforts in combating workload and job demands, companies need to carry out job training, communication, reward systems, inter-worker relations and a good working environment. QWL affects organizational commitment and loyalty, improving employees positive attitudes, increasing employees intrinsic productivity and motivation, improving corporate effectiveness and competitive in the face of global business as well as the quality of employee life. These variables may affect performance of individual as well as organizational performance. Keywords: Quality of work life, human resources, performance